Development of a GridPix X-ray polarimeter. Issue 1 (1st November 2022) - Gruber, Markus; Desch, Klaus; Kaminski, Jochen; Richarz, Leonie
Abstract : In gaseous detectors it is possible to determine the polarization of an X-ray beam by tracking photoelectrons which are created in photoelectric interactions of the photons with the gas molecules. Based on the differential cross section of this interaction the emission angle of the photoelectrons is correlated with the polarization plane of the beam. Depending on the photon energy and on scattering of the photoelectrons on gas molecules the length of the relevant part of the track is only in the order of a few hundred microns. Thus, a high tracking resolution is needed. This is achieved with the GridPix [1] - a combination of the highly granular Timepix pixel ASIC [2] and a photolithographically postprocessed MicroMegas called InGrid which holes are aligned with the pixels of the ASIC. Such a detector was operated in a testbeam at the P09 beamline [3] of PETRA III with a 99% linear polarized beam and a modulation factor of 77% was measured. Furthermore, tests of different gas pressures and different beam energies were performed.